Battered women in Botswana, Volume2 - Mogwe, Alice (African Gender Institute, 2026)
One of the aims of this comparative ·chapter is to provide the researcher with ideas for recommendations for her own situation. A brief excursus will be made into selected Zimbabwean legislation and its practical effect on the lives of women in that country.